A Role for Exercise to Counter Skeletal Muscle Clock Disruption. Issue 1 (January 2021) - Erickson, Melissa L.; Esser, Karyn A.; Kraus, William E.; Buford, Thomas W.; Redman, Leanne M.
Abstract : Disruption of the skeletal muscle circadian clock leads to a preferential shift toward lipid oxidation while reducing carbohydrate oxidation. These effects are apparent at the whole-body level, including glucose intolerance, increased energy expenditure, and fasting hyperglycemia. We hypothesize that exercise counters these metabolic disturbances by modifying the skeletal muscle clock and reverting substrate metabolism back toward an optimal substrate balance. Abstract : Exercise may mitigate cardiometabolic disease in part through actions on the skeletal muscle circadian clock.